A survey on proposed work-based learning (WBL) curriculum for animation programme in Faculty of Applied and Creative Arts : Perspectives from students, parents, and industry representatives - Terry, Lucas; Auzani Zeda, Mohamed Kassim; Natasha, Rusdy Wong; Jong, S.J; Tang, Hung Moi; Loh, Ngiik Hoon (Centre for Applied Learning and Multimedia, Universiti Malaysia Sarawak, 2024)
The work-based Learning (WBL) curriculum, a unique experiential learning academic programme, emphasizes a close collaboration between educational institutions and industry players. This approach offers students real-world working experience during their long-term industrial training. This study aims to gather perspectives from students, parents, and animation industry representatives on the proposed WBL curriculum for the animation program at the Faculty of Applied and Creative Arts (FACA), Universiti Malaysia Sarawak (UNIMAS). The study used online surveys to collect data from these groups, with different sets of questions tailored to each. The survey revealed key themes such as financial concerns and industrial training readiness for long-term commitment, and suggested ways to address these concerns to make a WBL-style programme more feasible. The study underscores the crucial role of the university and industry training partners in providing financial support, and the importance of their contribution. Strong commitment and collaboration from these stakeholders are crucial. The study provides insights and suggestions for similar academic programmes that may face the same context and challenges as the animation programme in FACA, UNIMAS.